2020
DOI: 10.32598/ijmtfm.v10i1.26639
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Poisoning and Its Treatment

Abstract: Background: Methanol is a toxic alcohol found in illegal liquor, and its poisoning may cause death if not treated timely and properly. In 2018, methanol toxicity in Iran increased dramatically. Regarding the high prevalence of methanol toxicity, its high mortality rate, and the cost of treatment as well as the importance of timely diagnosis in the treatment of this condition, we decided to review methanol toxicity, its signs, symptoms, diagnosis, and treatment.Evidence Acquisition: We searched for arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Still, the only thing different in our case is that there was an element of torture involved after intoxication [24]. In a case reported by Najari F et al describes a homicidal electrocution of an 8‐year‐old boy by his father due to marital issues by tying the toes of both limbs with a wire and connecting it with the current source [25].…”
Section: Discussionmentioning
confidence: 99%
“…Still, the only thing different in our case is that there was an element of torture involved after intoxication [24]. In a case reported by Najari F et al describes a homicidal electrocution of an 8‐year‐old boy by his father due to marital issues by tying the toes of both limbs with a wire and connecting it with the current source [25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in treatment opportunities, the rates of morbidity and mortality in MP are still high. Because the findings of MP differ from person to person, the diagnosis is established late, thus, the treatment is initiated late, which contributes to increased morbidity and mortality rates (3,4,9). It is of great importance to quickly diagnose and treat this poisoning in EDs.…”
Section: Discussionmentioning
confidence: 99%
“…In industries, methyl alcohol can be found in cleaning materials, carburetor cleaners, antifreeze, photocopying liquids, chemicals such as paint and wax, glass cleaning solutions, model aircraft fuels, modified cars, alternative fuels, and homemade moonshine (2). It is reported that the use of hand disinfectants and cologne due to the COVID-19 outbreak may cause methyl alcohol poisoning (3). Methyl alcohol poisoning (MP) is an important emergency that can lead to severe morbidity and mortality (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies pointed to the high mortality rates associated with opioids overdose with respiratory depression as the primary cause (Larochelle et al,2018;Greene et al, 2019). Similarly, methanol toxicity is capable of producing end organ damage primarily due to formic acid formation (Ashurst and Nappe, 2019;Kaewput et al, 2020;Najari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%